ArgR-dependent bacterial resistance to host lipid droplets in Edwardsiella piscicida - Yue Peng; Yihan Liu; Junze Wu; Yuanxing Zhang; Qiyao Wang; Shuai Shao (Communications Biology)
Abstract Lipid droplets (LDs), as innate immune hubs, function in the front line of antimicrobial defense involved in the host-pathogen arms race. Particularly for intracellular bacterial pathogens, the endowed capacity to resist host LDs can effectively facilitate pathogen in vivo colonization and evasion from the host’s innate immune response. Here, to investigate the genetic mechanisms of intracellular bacteria response to host LDs, we utilized transposon insertion sequencing to dissect critical fitness determinants of Edwardsiella piscicida under the treatment of LDs isolated from its native host, turbot. Targeted metabolomics indicated that LD challenge resulted in the accumulation of intracellular arginine. The core arginine metabolism regulatory factor, ArgR, was found to play a pivotal role in combating LDs, emphasizing the importance of orchestrating intracellular arginine levels for bacterial LD adaptation. Specifically, ArgR enhanced the expressions of genes involved in arginine catabolism (speA/B and arcC) and diminished gene transcripts associated with arginine import (artP) and synthesis (argD/E/H). Furthermore, ArgR contributed to the pathogenesis of E. piscicida, promoting the proliferation in host cells and virulence in turbot. Collectively, our results shed light on the underlying mechanism of intracellular pathogens resisting LDs during bacterial infections and highlighting the crucial role of arginine in the host-pathogen interactions.